DEVELOPMENT OF METAVERSE LEARNING SPACE TO IMPROVE THE VISUALIZATION OF ABSTRACT CONCEPTS IN PHYSICS LEARNING - Ahmad Fahrudin; Fatkhur Rohman; Eka Maryam (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
Physics education in college is often faced with the great challenge of conveying abstract concepts such as quantum mechanics and relativity. In response to these challenges, this research developed a Metaverse Learning Space (MLS) that aims to improve the visualization and understanding of these abstract concepts. This research uses the ADDIE development method, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 50 students from the Computer Systems Engineering (RSK) study program at Bina Insan University. Through the use of MLS, pre-test and post-test results show a significant improvement in understanding of physics concepts. The results of the statistical test with the paired sample t-test show that MLS has a positive impact on student understanding. This research contributes to the development of technology-based learning methods to support a deeper conceptual understanding of the field of physics.